Mediation in marital discord in Islamic law: legislative foundation and contemporary application - Haneef, Sayed Sikandar Shah (2010)
Mediation as a method of marriage confl ict resolution has recently emerged as one of the most workable institutionalized techniques in Western jurisdictions. In Islamic law, although ipso facto, it was given legislative recognition centuries ago under the principle of taḥkim; its potential as a viable reconciliation technique was somewhat obscured by juridical technicalities. Indisputably, mediation was the underlying ratio legis for the institution of ḥakam (arbitration). In practice, however, mediation was not the sole prerogative of the arbitration. It was instituted and carried out through numerous culturally specifi c methods, both formal and informal. In the Malaysian scene, mediation in family dispute is part of the ongoing daily job of Shariah lawyers, judges and offi cers in religious departments. However, critiques believe that neither the agents under traditional ḥakam nor Shari`ah practitioners of Shari`ah bodies have the necessary training and soft skills to act as eff ective go-betweens in resolving marital confl icts in the contemporary setting. Th e alternative, therefore, is to create a body such as a “Conciliatory Committee” using the pattern for a Western mediation model. Th us this paper, while agreeing with this idea, proposes an integrated method of doing this within the hybrid framework of both arbitration and modern mediation techniques consistent with Islamic legal methodology.